2012
DOI: 10.1038/nn.3152
|View full text |Cite
|
Sign up to set email alerts
|

Cued memory reactivation during sleep influences skill learning

Abstract: Information acquired during waking can be reactivated during sleep, promoting memory stabilization. After people learned to produce two melodies in time with moving visual symbols, we produced a relative improvement in performance by presenting one melody during an afternoon nap. Electrophysiological signs of memory processing during sleep corroborated the notion that appropriate auditory stimulation that does not disrupt sleep can nevertheless bias memory consolidation in relevant brain circuitry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
237
3
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 293 publications
(264 citation statements)
references
References 24 publications
19
237
3
5
Order By: Relevance
“…This manipulation impaired trace eyeblink conditioning, a hippocampus-dependent learning task (Nokia et al 2012). Other studies in humans have shown that reactivation during SWS can enhance not only spatial memory but also procedural memories, suggesting that reintroduction of cues during sleep may reactivate other brain regions as well (Antony et al 2012;Oudiette et al 2013). These findings validate the hypothesis that NREM SWS is important for learning and memory (Girardeau et al 2009;Ego-Stengel and Wilson 2010).…”
Section: Sleep Enhances Memory Consolidationsupporting
confidence: 66%
“…This manipulation impaired trace eyeblink conditioning, a hippocampus-dependent learning task (Nokia et al 2012). Other studies in humans have shown that reactivation during SWS can enhance not only spatial memory but also procedural memories, suggesting that reintroduction of cues during sleep may reactivate other brain regions as well (Antony et al 2012;Oudiette et al 2013). These findings validate the hypothesis that NREM SWS is important for learning and memory (Girardeau et al 2009;Ego-Stengel and Wilson 2010).…”
Section: Sleep Enhances Memory Consolidationsupporting
confidence: 66%
“…This decision reflected a tradeoff between the increased prevalence of slow waves in SWS versus the reduced overall time of SWS that occupied in this experiment: only ϳ17% of sleep time compared with ϳ50% of sleep time in stage 2 (Table 1). Moreover, although SWS clearly plays a role in memory consolidation and reactivation (Plihal and Born, 1999;Mölle et al, 2004;Peigneux et al, 2004;Rasch et al, 2007;Aeschbach et al, 2008;Antony et al, 2012;Mascetti et al, 2013), such a role is also documented for stage 2 sleep (Gais et al, 2002;Schabus et al, 2004;Clemens et al, 2007;Nishida and Walker, 2007;Andrade et al, 2011;Arzi et al, 2012;Mednick et al, 2013;Tamminen et al, 2013 (Mednick et al, 2013). Given that the primary goal of this study was to ask whether sleep conditioning induces behavioral modifications that persist over time, and considering the increased number of events we could expect in stage 2 versus SWS, we concluded that stage 2 conditioning is a safer path for us to test.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, experimentally inducing memory reactivation by reexposure to a contextual olfactory memory cue during SWS activated hippocampal areas during sleep and resulted in improved memory recall the next day Rasch et al, 2007). This concept has received further support by recent findings indicating that reactivating memories during sleep by auditory cueing leads to a strengthening of individual memory traces, suggesting a high degree of specificity of the effects of reactivation on memory consolidation during sleep (Oudiette, Antony, Creery, & Paller, 2013;Antony, Gobel, OʼHare, Reber, & Paller, 2012;Rudoy, Voss, Westerberg, & Paller, 2009). Although a first study on creativity suggests that odor effects on reactivation are absent when different odors are used before and during sleep (Ritter, Strick, Bos, van Baaren, & Dijksterhuis, 2012), the specificity of olfactory cueing for memory consolidation processes during sleep has not yet been examined in previous studies.…”
Section: Introductionmentioning
confidence: 90%